The controlled creation of a maximally entangled state between a SQUID ring and a single electromagnetic field mode - Mark Everitt; T.D. Clark; J.F. Ralph; P.B. Stiffell (2010)
We consider a SQUID ring inductively coupled to an electromagnetic field mode, both treated quantum mechanically. We demonstrate a method for creating a maximally entangled state between the ring and the field mode. Our method utilises a non-adiabatic external magnetic flux pulse to move into and out of a transition region. Hence, our approach is fundamentally different to techniques based on Landau–Zener tunnelling that can also be used to achieve similar results. Our analysis is extended to include the effects of coupling the system to a dissipative environment. With this model we show that although such an environment makes a noticeable difference to the time evolution of the system, it need not destroy the entanglement of this coupled system over time scales required for quantum technologies.